Filing a Restraining Order in Florida - Kathleen Beall; Heidi Radunovich (EDIS)
After a charge or arrest for domestic violence, the abuser may still find ways to cause harm. One of the most common threats faced after ending a violent relationship is stalking. Stalking is when someone repeatedly follows, harasses, or makes threats against you. Fortunately, there are laws and legal protections that can work to keep you safe if you are stalked. The first and often most powerful of these protections is filing an injunction. In this 3-page fact sheet, Kathleen Beall and Heidi Radunovich explore what an injunction is, how it is filed, and what it protects you against. Published by the UF Department of Family, Youth and Community Sciences, December 2014. Photo: (iStock/Thinkstock.com)